2015
DOI: 10.1111/jeb.12693
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal flower size variation correlates with local pollinator size in a bumblebee‐pollinated herb,Prunella vulgarisL. (Lamiaceae)

Abstract: The influence of locally different species interactions on trait evolution is a focus of recent evolutionary studies. However, few studies have demonstrated that geographically different pollinator-mediated selection influences geographic variation in floral traits, especially across a narrow geographic range. Here, we hypothesized that floral size variation in the Japanese herb Prunella vulgaris L. (Lamiaceae) is affected by geographically different pollinator sizes reflecting different pollinator assemblages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
3
45
1
Order By: Relevance
“…Previous studies that have investigated flower size variations along an altitudinal gradient in mountainous environments have reported corresponding altitudinal variations in, for example, pollinator species composition and nectar robbing frequency (Hattori et al , 2015Nagano et al 2014;Kuriya et al 2015;Zhao & Wang 2015). In this study, we showed that the pattern of flower size variation along an altitudinal gradient differed between two Impatiens species growing in similar habitats.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…Previous studies that have investigated flower size variations along an altitudinal gradient in mountainous environments have reported corresponding altitudinal variations in, for example, pollinator species composition and nectar robbing frequency (Hattori et al , 2015Nagano et al 2014;Kuriya et al 2015;Zhao & Wang 2015). In this study, we showed that the pattern of flower size variation along an altitudinal gradient differed between two Impatiens species growing in similar habitats.…”
Section: Discussionmentioning
confidence: 49%
“…The primary flower visitor to I. noli-tangere was also B. diversus, as Tokuda et al (2015) also reported ( Table 1). The flower-pollinator size match often influences plant fitness more than other factors Kuriya et al 2015). Therefore, these results suggest that flower dimensions were affected not by a clinal change in any abiotic environmental factor along altitude but by the size-match between the flowers and the B. diversus body size.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations